2022
DOI: 10.3390/en15145254
|View full text |Cite
|
Sign up to set email alerts
|

Combined Control System for the Coordinates of the Electric Mode in the Electrotechnological Complex “Arc Steel Furnace-Power-Supply Network”

Abstract: To stabilize the electrical mode of an arc steelmaking furnace in the initial stages of melting, it is advisable to use a high-speed current-limiting system, in addition to the traditional electrode movement control system. This system is implemented by including the primary winding of the furnace transformer choke, controlled by thyristors. The use of such a system, on the one hand, reduces the negative impact of the arc steel furnace on the the power supply network operation and, on the other, affects the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The system model presented in [24] was used for the study. The adequacy of this model is confirmed by the coincidence of the obtained results with the results of experimental studies and the results of theoretical calculations obtained by other authors [15,24]. The model uses the representation of the EAF elements (power grid M, furnace transformer TR, electric line with arc SL) in the form of multipoles.…”
Section: Mathematical Model Of the Electrical Complex "Power Supply N...supporting
confidence: 60%
See 1 more Smart Citation
“…The system model presented in [24] was used for the study. The adequacy of this model is confirmed by the coincidence of the obtained results with the results of experimental studies and the results of theoretical calculations obtained by other authors [15,24]. The model uses the representation of the EAF elements (power grid M, furnace transformer TR, electric line with arc SL) in the form of multipoles.…”
Section: Mathematical Model Of the Electrical Complex "Power Supply N...supporting
confidence: 60%
“…Today, the technological solutions are provided by such leading companies as Siemens (SIMETAL system), Danieli (HI-REG and Q-REG+ systems), and others. A commonly applicable "standard" strategy for controlling the electrical mode of EAFs is the formation of an "impedance control principle" [3,14,15]. Such a control system is based on phase voltage and current signals.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the coefficients of mutual influences between the phases of an electric arc furnace, we use the model of the system described in [32,50]. The adequacy of this model is confirmed in [32,50] based on the coincidence of the obtained results with the results of experimental studies and the results of theoretical calculations obtained by other authors.…”
Section: Mathematical Model For Conducting Researchmentioning
confidence: 88%
“…Wrong movements of electrodes may occur in phases in which the arc length has not changed, and the variation in the current is due to the mutual influence among the phases of the three-phase system [31]. When a high-speed current loop based on an adjustable inductor is used in the system, there is mutual influence between the mentioned loop and the electrode movement control system [32,33]. Stabilization of the current using a high-speed circuit leads to a reduction in the speed of the disturbance response by the electrode movement circuit in the phase where the disturbance occurred, but false electrode movements are reduced in other phases.…”
Section: Introductionmentioning
confidence: 99%
“…A feature of the proposed mathematical model of the switch control-based multi-winding IM is using the method of the average voltages in the integration step (AVIS) [25][26][27]. This method has repeatedly been used by authors, and its high efficiency was demonstrated during a simulation of power schemes with synchronous machines and induction machines, as well as power systems with nonlinearities [26,[28][29][30]. The advantages of the method are high calculation speed and numerical stability, which make it suitable for creating real-time models.…”
Section: Mathematical Model Of Multi-winding Immentioning
confidence: 99%